The study of multilayer coatings based on MoN(MoZr)ZrN and (TiMo)N/(TiMo), (CrZr)N/(CrZr) obtained by the method of vacuum-arc deposition - R.E. Sakenova; N.K. Erdybaeva; A.D. Pogrebnjak; M.K. Kylyshkanov (Қарағанды университетінің хабаршысы. Физика сериясы)
In the article the results of experimental studies of multilayer coatings MoN(MoZr)ZrN and (TiMo)N/(TiMo), (CrZr)N/(CrZr), obtained on A570 Grade stainless steel samples with a Ra roughness of up to 0.09 µm are presented. Coatings were formed by vacuum-arc evaporation of cathodes in the installation Bulat-6. After deposition of multilayer coatings by scanning electron microscopy and microanalysis, a nonuniform distribution of zirconium, chromium, nitrogen and molybdenum was found on the surface of the samples.The research results show that good tribological properties in combination with improved physicomechanical properties make the deposited material promising for use as a protective material for machines and tools operating in extremely difficult working conditions.